Komunikasi Sosial Program Pembangunan Masyarakat Dalam Perspektif Terkini - Susan Daniel (FKIP Universitas Palangka Raya, 2021)
Development is a process that does not only include physical and material improvement, but is also a social change that requires broadly participatory social equity to promote social and material conditions including greater justice, freedom, and high quality values ​​through the acquisition of greater control. great for the environment. The development process involves operating communications for its sustainability. The development movement directs the sub-systems within the development entity to move in line with the development goals. One of the sub-systems is communication and information. Development communication undergoes a dynamic process that leads to a more interactive and participatory form.